Ethnobotanical study on the use of medicinal plants to treat cardiovascular diseases in the Fez-Meknes region of Morocco - El Moumen, Bouchra; Yamni , Majda; Touijer, Hanane; Hadi , Nadia; El Karkouri , Jamila; Fadili , Kamal; Asserraji , Rym; Bouqbis , Laila; Louafi, Boutaina; Zair, Touriya (Ethnobotany Research and Applications, 2025)
Background: Cardiovascular diseases represent a major global issue. The Moroccan population possesses ethnobotanical knowledge passed down through generations, enriched by ethnic diversity. The Fez-Meknes region has various aromatic and medicinal plants that can be utilized in multiple ways across several fields. The objective of this study focuses on identifying and collecting data on medicinal plants used to prevent diabetes, hypertension, obesity, atherosclerosis, and hypercholesterolemia, considered the main risk factors for cardiovascular diseases. Methods: Data collected through surveys of 270 participant were analyzed using four quantitative indices: relative frequency of citation (RFC), fidelity level (Fl), informant consensus factor (ICF), and the most used part (PPV). Results: The study revealed the presence of 80 species belonging to 41 botanical families. The most frequently reported families were Lamiaceae (47%), followed by Fabaceae and Apiaceae (29%). Hypertension had the highest informant consensus factor (ICF) among the treated diseases at 0.923. The survey also showed that leaves were the most used part of the plants (PPV = 32.9%), and maceration were the most common preparation (23.91%). Conclusions: This study contributes to the exploration and documentation of traditional practices in order to better understand and valorize their therapeutic potential. Further research, combining ethnobotanical knowledge with rigorous scientific analysis, could lead to the development of new strategies for the prevention and treatment of cardiovascular disease. Keywords: Ethnobotanical study, cardiovascular diseases, traditional medicine, Fez-Meknes, Morocco.